2016
DOI: 10.1021/acs.macromol.6b01291
|View full text |Cite
|
Sign up to set email alerts
|

19F Double Quantum NMR Spectroscopy: A Tool for Probing Dynamics in Proton-Conducting Fluorinated Polymer Materials

Abstract: Solid-state NMR spectroscopy is an important technique for probing the structure and local dynamics of materials at the molecular level. For example, 1H double quantum (DQ) NMR is a well-established probe of local dynamics. Here, this concept has been extended to characterize fluorinated ionomer materials for the first time. 19F DQ recoupling NMR experiments are applied to investigate the site-specific local dynamics of the polymer electrolyte material, Nafion 117, under various conditions with respect to temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Moreover, the 19 F DQ build‐up curve shows a maximum for tDQ12 µs. The static value Dstat of the apparent 19 F‐ 19 F dipolar couplings for the vicinal fluorines of the backbone CF 2 groups, which are the major types of fluorine present in our P(PDV‐co‐HFP) copolymer, are was recently calculated for Nafion and a value 16.06 kHz was obtained . Interestingly, the value true(2π×Dstattrue)110 µs is very close to the tDQ at the maximum of the 19 F DQ build‐up curve.…”
Section: Resultssupporting
confidence: 56%
“…Moreover, the 19 F DQ build‐up curve shows a maximum for tDQ12 µs. The static value Dstat of the apparent 19 F‐ 19 F dipolar couplings for the vicinal fluorines of the backbone CF 2 groups, which are the major types of fluorine present in our P(PDV‐co‐HFP) copolymer, are was recently calculated for Nafion and a value 16.06 kHz was obtained . Interestingly, the value true(2π×Dstattrue)110 µs is very close to the tDQ at the maximum of the 19 F DQ build‐up curve.…”
Section: Resultssupporting
confidence: 56%
“…The alternative PFSA materials, Aquivion98 (Figure b) and 3M-725 (Figure c), have not been studied in detail previously using 19 F SSNMR. Importantly, our meticulous deconvolution routine ,, is an effective tool for distinguishing the molecular structure of the PFSAs. In the spectra of all three PFSAs, the signal at −122 ppm is dominant, and is assigned to the backbone CF 2 moieties, which are the major building blocks of PFSAs.…”
Section: Resultsmentioning
confidence: 99%
“…It was discovered that the motional amplitude of the branches is greater in hydrated Nafion than that in dry samples. Later work based on the 19 F– 19 F double‐quantum effect (caused by 19 F– 19 F dipolar couplings) also confirmed that hydration has a greater effect on the branching sites …”
Section: Interfaces In Ionomers and Graphite Oxidesmentioning
confidence: 89%